Rheology and phase inversion behavior of polyphenylenesulfone (PPSU) and sulfonated PPSU for membrane formation. (2nd September 2016) - Feng, Yingnan; Han, Gang; Zhang, Liling; Chen, Shing-Bor; Chung, Tai-Shung; Weber, Martin; Staudt, Claudia; Maletzko, Christian
Abstract: Polyphenylenesulfone (PPSU) is widely used as a membrane material for water reuse applications because of its good chemical resistance, hydrolysis stability and outstanding mechanical strength. However, due to its hydrophobic nature, fouling and relatively low water permeability are potential drawbacks of PPSU membranes. Sulfonation of PPSU could significantly improve the hydrophilicity but compromise the mechanical strength. Moreover, the degree of sulfonation has great influences on the solution properties of the sulfonated PPSU (sPPSU) dopes. This study aims to investigate the rheological properties and phase separation behavior of PPSU and sPPSU polymers with various degrees of sulfonation, and disclose their molecular-level interactions. With relatively low degrees of sulfonation, sPPSU polymers exhibit much larger viscosity and dynamic moduli than PPSU, particularly at higher polymer concentrations. The sPPSU polymers also possess greater non-solvent (i.e., water) tolerance and display delayed demixing behavior for phase inversion. Molecular dynamics (MD) simulation shows that the π–π stacking of aromatic rings and hydrogen bonding among the sulfonic acid groups are the main interactions between the polymer molecules. The flat-sheet sPPSU membranes cast by the non-solvent induced phase separation (NIPS) method exhibit high water permeability with morphology closely correlated to the rheological properties and phase inversion characteristics of the polymer solutions. This fundamental study may provide pertinent insights of design strategies to prepare hydrophilic membranes from sulfonated polymers. Graphical abstract: Highlights: sPPSU polymer solutions show enhanced rheological properties than PPSU solutions. Sulfonic acid groups in sPPSU induce higher water tolerance and delayed demixing. Higher degrees of sulfonation suppress formation of macrovoids in sPPSU membranes. π–π stacking and hydrogen bonding between PPSU and sPPSU molecules are revealed.